A comparative study of the attitudes of elementary school teachers, principals and district supervisors toward supervisory pratices in the Division of La Union - Eslao, Rufino O. 1933- ([Quezon City publisher not identified], 1960)
The purpose of this study is to compare the attitudes of the elementary school teachers, elementary school principals, and district supervisors toward supervisory practices, and to present the reasons behind their attitudes.
Bibliography: l. [240]-243.
Thesis (Master in Education)--University of the Philippines, 1960
Typescript (carbon copy)
Vita
Keywords: Teachers -- La Union; School superintendent and principals; School supervision